Last of the glow worms : memoir of a nuclear weapons technician at the end of the cold war - Woodward, Jeff (McFarland & Company, Inc., 2017)
From the early 1950s until 1992, the U.S. Army deployed thousands of nuclear warheads throughout Europe as a deterrent to Soviet ambitions. The end of the Cold War saw the decommissioning of much of the U.S. nuclear arsenal and the phasing out of support personnel. This memoir by one of the Army's last "glow worms" chronicles his career as a nuclear weapons specialist--from 17-year-old recruit to participant in Operation Silent Echo, codename for the removal of all tactical warheads throughout Asia and Europe
Keywords: Warheads -- United States -- History.; Nuclear weapons -- United States -- History.; United States -- Armed Forces -- Equipment.; United States -- Armed Forces -- Foreign countries.; HISTORY -- Military -- Other.; TECHNOLOGY & ENGINEERING -- Military Science.; Armed Forces; Armed Forces -- Equipment and supplies; Nuclear weapons; Warheads; United States; Electronic books.; History